Pengaruh Penggunaan Teknologi Berbasis Artificial Intelligence (ChatGPT) terhadap Minat Belajar dan Hasil Belajar Matematika Siswa SMA Swasta KOTA TEBING TINGGI - Putri, Khairunnisa Putri; Haryanto, Haryanto (Ranah Research : Journal of Multidisciplinary Research and Development, 2026)
This study aims to examine the effect of using Artificial Intelligence-based technology (ChatGPT) on students’ learning interest and mathematics learning outcomes in private senior high schools in Tebing Tinggi. The integration of AI in education is increasingly seen as a promising approach to support learning processes, particularly in enhancing student engagement and academic achievement. Therefore, understanding its impact is essential for improving the quality of mathematics instruction. This study used a quantitative approach with a quasi-experimental research design. The population consisted of students from five private senior high schools in Tebing Tinggi. The sample was selected using random sampling, involving eleventh-grade students from R.A. Kartini Private Senior High School and Tamansiswa Tebing Tinggi Private Senior High School. The instruments included a learning interest questionnaire and a mathematics achievement test, both validated through expert judgment and tested for reliability using Cronbach’s Alpha. Data analysis was conducted using MANOVA to examine the simultaneous effects of the variables. The results show that the significance value from the MANOVA test is 0.000 (< 0.05), indicating that the use of Artificial Intelligence-based technology (ChatGPT) has a significant simultaneous effect on both students’ learning interest and mathematics learning outcomes. These findings suggest that integrating AI technology into mathematics instruction enhances student engagement and improves learning achievement. This study highlights the potential of AI-based tools as an innovative alternative to support more effective and meaningful learning in mathematics education.